FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN REMAJA DALAM MENGGUNAKAN HELM PADA SISWA SMA NEGERI 4 KOTA KUPANG - Juan Devis Liunesi; Marylin Junias; Soni Doke (CHMK HEALTH JOURNAL, 2022)
Adolescent adherence to wearing helmets can reduce the risk of harm caused by traffic accidents. This study aims to determine the factors associated with adolescent adherence to wearing helmets in SMA Negeri 4 Kota Kupang. The time of this research was carried out from February 01, 2020 to February 20, 2020. The method used in this research is an analytical method using a cross-sectional approach. The population in this study amounted to 113 teenage students who use motorbikes to school and The sample consisted of 53 people who were determined using simple random sampling and then used the proportional random sampling technique to determine the number of samples for each class. Furthermore, the data were analyzed using chi_square analysis. The results showed that the variables that had a relationship with adolescent adolescents' compliance in using helmets were among others, the attitude variable (p-value = 0.007), the helmet availability variable (p-value = 0.020), and the rule variable (p-value = 0.000). Meanwhile, the variables that did not have a relationship with adolescent adolescents' compliance in using helmets were the knowledge variable (p-value = 0.377) and the age variable (p-value = 0.655). Keywords: Compliance, Youth, Helmet Use.